Lebanon - The Insurance Sector : A Market and Risk Based Review - World Bank (Washington, DC, 2014)
This note summarizes the conclusions of the review of the insurance sector in the Lebanon as part of the Financial Sector Assessment Program (FSAP). The main objectives of the assessment are to review the performance and structure of the insurance sector with respect to: the potential exposure of the sector to vulnerabilities, either generated from the sector or in response to other circumstances outside the sector that could either be magnified or dampened by the sector; the potential for the sector to grow and develop, in its own context and also to contribute to the overall long term growth and development of the economy and the well-being of the Argentine people; and the relationship between the oversight and regulatory arrangements for the sector against international norms and best practices. The note focusses, primarily, on the 'developmental' objective. The note is prepared in varying levels of detail selectively identifying then developing issues and based firmly in an analysis of the existing market situation and performance. The insurance sector is material compared to other markets in the region but small by worldwide standards. The sector has grown in nominal and real terms supported by growth in motor and medical insurance. Life insurance growth has been supported by the development of a bancassurance model, including the introduction of single premium credit life products.